Teachers’s Development for learning management in the 21st century at private school in Phang-Nga Province - Hassanee , Thida (Al-HIKMAH Journal, 2024)
This study employed a mixed methods research approach with the following objectives:1) To investigate the professional development of teachers in private Islamic schools in Phang Nga province for the 21st-century learning management. 2) To examine the problems and suggestions for the development of teachers in private Islamic schools in Phang Nga province for 21st-century learning management. 3) To explore strategies for the development of teachers in private Islamic schools in Phang Nga province for the 21st-century learning management. The sample group consisted of 103 individuals, including staff from private schools in Phang Nga province affiliated with the Provincial Education Office. The sample size was determined using Krejcie and Morgan's table (Krejcie& Morgan, 1970: 607-610). The research utilized questionnaires as the research instrument and employed statistical analysis methods including frequency, percentage, mean, and standard deviation for data analysis. The research findings indicated that 1) the overall level of professional development of teachers in private Islamic schools in Phang Nga Province for the 21st-century learning management was in high level. Ranked from high to low average, the highest average score was in the area of implementation, followed by teacher assessment and improvement, while the lowest score was in planning. 2) Challenges in developing teachers for the 21st-century learning management in private Islamic schools in Phang Nga Province found that the teachers lacked learning and skills focused on fostering student competencies, such as the use of new technologies, material design, and innovation for learning management. Recommendations for teachers’ development for the 21st-century learning management, the result showed that teachers should receive targeted training aligned with their subject areas. Educational field trips should be organized to exemplary schools that have successfully implemented the 21st-century learning management and be accepted by society and enhancing teachers’ skills in information technology and some up-to-date innovations. 3) Strategies for developing teachers in private Islamic schools in Phang Nga Province for the 21st-century learning management, the research indicated that 1) in planning, stablished clear policies and development plans for teachers aligned with the 21st-century learning management and allocated resources and budget appropriately to ensure adequate and suitable teacher development. 2) For the implementation, the result revealed that the schools should conduct training programs tailored to specific subject areas in real-world or practical settings which allowing teachers to visualize and effectively apply what they have learned to enhance their efficiency. 3) In monitoring and evaluation, the study found that schools should have continuous and systematic monitoring and evaluation of teachers’ development.4) In the area of improvement and correction, schools should analyze data from the monitoring and evaluation to identify areas needing enhancement in the next phase of teachers’ development. Fostering communication and collaboration among teachers was essential for their self-improvement in various aspects of their work. Utilizing feedback data could enable continuous improvement to ensure teachers' work becoming more effective moving forward.